Mídia e educação: representações culturais de professoras e professores da educação básica. - Balla, Cristiane de Bastiani (2016)
This research aims at the representations, discussing the media in the educational field, more specifically in the school. It investigates how the teachers represent and produce meanings about the insertion of the media in their educational action, thereby problematizing the media, their representation in the education and pedagogical practice of teachers in a public basic education school. It also investigates how the school in the face of contemporary society, which influences cultural identity, offers different means of socialization, while at the same time promoting the decentering of culture. The research, of a qualitative nature, is based on theoretical references whose conception contemplates the Cultural Studies. This theoretical field has roots in cultural materialism, as it encompasses the media as well as media analysis and has a great contribution by researchers who investigate these relationships by forming an eminently interdisciplinary field. As a methodology it is proposed semi-structured interviews aimed at a group of teachers in order to know in the first approximation their representations about the insertion of the media in the educational context followed by data analysis that subsidized the answer to the initial problem of the research, Which asks: "How do teachers represent and produce meanings about the insertion of the media into their educational action? The results of the analysis of the interviews showed that the insertion of the media in the school spaces can contribute in a significant way with the improvement of the learning as well as, access to science through its varied means contributing to both students and teachers in their organization of pedagogical work.